The Lake Poets and Professional Identity - Goldberg, Brian (Cambridge University Press, 2013)
When William Wordsworth, Robert Southey, and Samuel Taylor Coleridge – the Lake school – formulated their earliest descriptions of the role of the poet, two models of vocational identity exerted special pressure on their thinking. One was the idea of the professional gentleman. In their association of literary composition with socially useful action, their conviction that the judgment of the poet should control the literary marketplace, and their efforts to correlate personal status with the poet’s special training, the Lake writers modified a progressive version of intellectual labor that was linked, if sometimes problematically, to developments in the established professions of medicine, church, and law. In short, they attempted to write poetry as though writing poetry could duplicate the functions of the professions. The other model, and it is related to the first, is literary. Like the Lake poets, earlier eighteenth-century authors had been stimulated, if occasionally frustrated, by the puzzle of how to write poetry in the face of changing conceptions of intellectual work.